Analisis Proses Pelaksanaan Pembelajaran Keterampilan Tata Boga Membuat “Kue Pastry” bagi Warga Belajar Paket C Kelas XI IPS di SPNF SKB Kota Samarinda - Atikah Maulidah (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2020)
In general, the learning process is only related to academic learning. However, it is different from culinary skills which are generally only implemented if there is training or activities that lead to specific training. However, in SPNF SKB Samarinda City implements culinary skills as learning is routinely carried out even into the curriculum so that it has a Learning Implementation Plan (RPP). The purpose of this study was to determine the implementation of learning culinary skills to make a